2016
DOI: 10.1007/s10072-016-2523-z
|View full text |Cite
|
Sign up to set email alerts
|

Intractable pruritus in neuromyelitis optica

Abstract: Neuromyelitis optica (NMO) is an immune-mediated disease of the central nervous system. Pruritus in patients with NMO has rarely been reported. We aimed to explore the characteristics and underlying mechanisms of pruritus in NMO patients. We reviewed the case records of 64 NMO patients who visited the Department of Neurology at the Third Hospital of Sun Yat-sen University between 2009 and 2015. Of the 64 aquaporin-4 antibody-positive NMO patients, 18 had pruritus. Spinal magnetic resonance imaging (MRI) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“… 75 In this regard, Xiao et al retrospectively analyzed 64 Chinese NMOSD patients who were AQP4-IgG positive, and found that 28% (18/64) of these patients had the symptom of pruritus. 76 Furthermore, recent studies have reported identical findings and further revealed that pruritus can be detected as an initial symptom before the attack. Hence, this may indicate a new episode of myelitis in patients with NMOSD.…”
Section: The Complexity and Wide Range Of Nmosdmentioning
confidence: 68%
See 1 more Smart Citation
“… 75 In this regard, Xiao et al retrospectively analyzed 64 Chinese NMOSD patients who were AQP4-IgG positive, and found that 28% (18/64) of these patients had the symptom of pruritus. 76 Furthermore, recent studies have reported identical findings and further revealed that pruritus can be detected as an initial symptom before the attack. Hence, this may indicate a new episode of myelitis in patients with NMOSD.…”
Section: The Complexity and Wide Range Of Nmosdmentioning
confidence: 68%
“…This reflects the typical centralized location of lesions in the spinal cord that affects dorsal horn neurons and gray matter in patients with NMOSD. 76 A third possible mechanism may be that neurons involved in the regulation of neuropathic pruritus may highly express AQP4, and thereby be preferentially involved in NMOSD. 75 …”
Section: The Complexity and Wide Range Of Nmosdmentioning
confidence: 99%
“…Recently, pruritus has been reported as a common symptom in neuromyelitis optica (NMO)/NMOSD patients, particularly in relapses of longitudinally extensive transverse myelitis (LETM). 14…”
mentioning
confidence: 99%
“…In addition, pruritus may be observed as a first symptom in NMOSD patients, even before other neurological disorders. 14…”
mentioning
confidence: 99%
See 1 more Smart Citation